Information and Communication Technologies in Tourism 2019 2018
DOI: 10.1007/978-3-030-05940-8_22
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Protection in Tourism: Where We Are and Where We Should Be Heading For

Abstract: The link between information privacy concerns and privacy behaviours has been a focus of extensive investigation in various disciplines. However, little attention has been devoted to this issue in the tourism literature. Spurred by technological development and shaped by tourismrelated environments, emerging privacy issues call for comprehensive yet context-specific studies to ensure tourists are making beneficial privacy choices. This paper first presents a comprehensive review of state-of-the-art research on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 43 publications
1
34
0
1
Order By: Relevance
“…Other risks are associated with constant collection of sensitive personal data, including biometric and behavior data, resulting in issues of privacy, in terms of both identifiability and surveillance, and security. Additionally, tourists may not be aware of the range of privacy and security threats associated with automated systems powered by artificial intelligence technologies(Tussyadiah, Li, & Miller, 2019), making them prone to making uninformed privacy decisions.The rapid development of artificial intelligence and its related technologies should be balanced with strategies and policies that endeavor to optimize the benefits and minimize the risks of intelligent automation in tourism. These might include training the current workforce in new skills, implementing educational reform, creating new safety and security standards for intelligent automation, informing tourists about privacy issues, and creating standards for transparent and responsible use of customer data.…”
mentioning
confidence: 99%
“…Other risks are associated with constant collection of sensitive personal data, including biometric and behavior data, resulting in issues of privacy, in terms of both identifiability and surveillance, and security. Additionally, tourists may not be aware of the range of privacy and security threats associated with automated systems powered by artificial intelligence technologies(Tussyadiah, Li, & Miller, 2019), making them prone to making uninformed privacy decisions.The rapid development of artificial intelligence and its related technologies should be balanced with strategies and policies that endeavor to optimize the benefits and minimize the risks of intelligent automation in tourism. These might include training the current workforce in new skills, implementing educational reform, creating new safety and security standards for intelligent automation, informing tourists about privacy issues, and creating standards for transparent and responsible use of customer data.…”
mentioning
confidence: 99%
“…However, the results demonstrate that awareness about personalisation technology being implemented increases tourists' concerns about the accuracy of personalisation as well as the security and misuse of their personal data. In other words, the awareness about personalisation intensifies the personalisation-privacy paradox of the tourist co-creation behaviour [5].…”
Section: Discussionmentioning
confidence: 99%
“…Legal regulations, such as the General Data Protections Regulation (GDPR), and widely discussed data breaches and misuses by Cambridge Analytica, Cathey Pacific, Marriott and other tech-savvy companies, have in fact exposed the threats of privacy intrusion and frauds, which data-driven personalisation can pose [4]. Given that personalisation is named among the key success factors for tourism businesses, practical solutions are required to ensure positive tourists experiences [5]. However, the effect of information about data-driven personalisation on tourist experiences remains underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Macroenvironmental factors, such as cross-cultural preferences, have been identified as antecedents of privacy concerns (Ioannou et al, 2020;Tussyadiah et al, 2019). Research on privacy has shown that culture impacts consumers' attitudes toward privacy concerns (Bellman et al, 2004;Cullen, 2009;Dinev et al, 2006;Milberg et al, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%